Nutritional Features of Biryani as The Basis for The Formation of An Entrepreneurial Mode in Biryani Market - Umachandran, Dr. Krishnan; Sawicka, Barbara; Nasir, Noori Abdul-Nabi; Pasqualone, Antonella (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Biryani is a traditional spice-flavored rice-based delicacy containing meat and vegetables. In this paper, the preparation of Biryani, its composition, nutritional value and entrepreneurial possibilities are discussed. The nutritional value per 100 g of product of different types of Biryani is given. A diagram of the cooking procedure of this dish is presented. The Biryani market is compared with the fast food market. Attention is also paid to the most important economic factors that influence the consumer’s decision when buying food. These are: per capita income, price of the food relative to other products, as well as changes in the size and structure of the population. An additional advantage over the competition is outside the links between the restaurants and customers, business partners and suppliers. The purchase of this dish is most often associated with the processes of interacting with customers, with consumer safety, shaping their expectations, market information and customer behavior. This research suggests how establishing a modern Biryani market. Experimenting new variants of this dish and taking advantage of innovative digital solutions could be a strategy for promoting entrepreneurial development and even reducing youth unemployment.